Studi Tentang Wirausaha Baru Berbasis Partisipasi Masyarakat Di Sulawesi Utara - Pio, Riane Johnly; Montolalu, Johny (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstrak. This research aims to identify the conditions and problems confronting the new entrepreneurs in managing the business.  This research uses descriptive analysis with the total sample as much of the 265 respondents. Data collected by use questioner and interview technique base on criteria that have been determined.  The research found that the business of trading as the main type of business, the mayority of high school educated respondents, initial capital came from businessmen themselves, generally they have not followed entrepreneurial training. This new entrepreneurial expects the government provides access to capital and training to support their efforts.  This research has limited because only identify new entrepreneurial activity and knowing perception them about government role of entrepreneurs beginners.  This research early to tell further research and information for strategic decision makers in the micro and small enterprises. Kata Kunci: Entrepreneurship, New Entrepreneurial, Micro and Small Enterprise